1997
DOI: 10.1038/sj.sc.3100393
|View full text |Cite
|
Sign up to set email alerts
|

Assisted reach and transfers in individuals with tetraplegia: towards a solution

Abstract: The purpose of this study was to investigate the in¯uence of a prototype trunk orthosis to assist an individual with tetraplegia. A single case study (26 year old male, C5 motor complete) using an interrupted time series analysis was conducted to investigate the individual's ability to reach, forward and laterally, and transfer with and without the orthosis. All tasks were performed on an AMTI 1 force platform in the long sitting position, with landmarks of the trunk and limbs recorded using Peak Performances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Curtis et al 47 using kinematic analysis reported that subjects with paraplegia were more e ective in performing a modi®ed functional reach task when they used a stabilization strap. 47 Kamper et al 48 used kinematic and center of pressure analysis to compare the lateral postural stability of individuals with SCI and nonimpaired subjects during sudden perturbations. They reported that all non-impaired subjects maintained stability with all perturbations, while all individuals with a SCI failed to maintain stability when exposed to higher-level perturbations.…”
Section: Research On Ue Function During Transfer-related Tasksmentioning
confidence: 99%
“…Curtis et al 47 using kinematic analysis reported that subjects with paraplegia were more e ective in performing a modi®ed functional reach task when they used a stabilization strap. 47 Kamper et al 48 used kinematic and center of pressure analysis to compare the lateral postural stability of individuals with SCI and nonimpaired subjects during sudden perturbations. They reported that all non-impaired subjects maintained stability with all perturbations, while all individuals with a SCI failed to maintain stability when exposed to higher-level perturbations.…”
Section: Research On Ue Function During Transfer-related Tasksmentioning
confidence: 99%
“…11 As a result, preliminary work to increase trunk stability during transfer activities through the use of a prototype trunk orthosis and orthotic device to facilitate transfers has been initiated. 12,13 Individuals with SCI often have to transfer toward an elevated surface (eg bed transfers, car transfers, floor to wheelchair transfers using a push-up technique, climbing up stairs using a push-up technique). It is suggested that transferring toward an elevated surface might be more challenging than transferring on an even surface for individuals with SCI because of the mechanical disadvantages associated with this particular task.…”
Section: Introductionmentioning
confidence: 99%
“…Postural instability may hinder the ability to perform transfers as well. 5 Seated balance may also be challenged when these dynamic forces are externally applied. This is the focus of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have described improved performance with the addition of trunk orthoses or belts. 2,5,7 However, use of these items is limited due to unwanted restrictiveness as well as di culty in donning and do ng the current designs.…”
Section: Introductionmentioning
confidence: 99%